Pengaruh Kombinasi Limbah Jagung Ketan (Zea mays ceratina) dan Kotoran Sapi pada Proses Pengomposan dengan Bioaktivator Berbeda di Desa Lokasari - I Gede Yoga Juni Sastrawan; I Putu Surya Wirawan; Ni Luh Yulianti (Program Studi Teknik Pertanian dan Biosistem, Fakultas Teknologi Pertanian, Universitas Udayana, Badung, Bali, Indonesia, 2023)
The potential waste of glutinous corn, cow dung, and local microorganisms (MOL) has not been utilized properly in Lokasari Village. Simple technology can use as a material for composting agricultural waste. This study aims to obtain the effect of the combination of material composition with the addition of different types of bioactivators on the quality of the composting results according to the Indonesian National Standard (SNI) 19-7030-2004. Compost ingredients are glutinous corn waste and cow dung. The bio activator materials used are banana weevil, Gamal leaves, and stale rice with a fermentation process for 2 weeks with the addition of molasses and rice washing water. The container used is a tubular bamboo basket with a height of 40 cm and a diameter of 40 cm. The research method used a two-factor factorial randomized block design. The first factor is the combination of the composition of glutinous corn waste and cow dung with 5 treatment levels, there are K1 (100%:0%), K2 (75%:25%), K3 (50%:50%), K4 (25%:75% ), and K5 (0%:100%). The second factor is the type of bio activator with 3 treatment levels, there are B1 (MOL banana weevil), B2 (MOL Gamal leaf), and B3 (MOL stale rice). The results showed that the combination of glutinous corn waste and cow dung with different types of bio activators had a very significant effect on temperature and C-organic, and significantly different on yield, N total, and C/N ratio. The composition of glutinous corn waste and K5B1 cow dung produced compost with the best average quality meeting SNI standards, there are pH 6.94, water content 36.47%, C-organic 28.87%, N-total 1.56%, and C/N ratio 18.49%.